Persistent Mortality Risk From Device-related Healthcare-associated Infection in Kidney Transplant Recipients Despite Multifaceted Interventions Action Calls for a Zero-tolerance Policy - Maria Bethânia Peruzzo, MD; Luana Oliveira Calegari, MSc; Renato Demarchi Foresto, MD, PhD; Helio Tedesco-Silva, MD, PhD; José Medina Pestana, MD, PhD; Lúcio Requião-Moura, MD, PhD (Transplantation Direct)
Background. Although multifaceted control intervention actions (bundles) are highly effective in reducing the risk of device-related healthcare-associated infections (d-HAIs), no studies have explored their impact on the outcomes of kidney transplant recipients (KTRs) or the extent of risk reduction achievable through the bundle implementation. Methods. Seven hundred ninety-eight prevalent KTRs admitted to the intensive care unit (ICU) requiring invasive devices were included: 449 patients from the bundle preimplementation period and 349 from the postimplementation period. The primary outcome was mortality within 90 d of ICU admission. Using Poisson regression models, the magnitude of risk reduction for d-HAIs after the bundle implementation and the impact of d-HAIs on the risk of death was estimated. Results. The 90-d survival rate was significantly lower in patients with d-HAIs (37.7% versus 71.7%; P < 0.001). The bundle implementation reduced the risk of d-HAIs by 58% (relative risk, 0.42; P = 0.005). Despite the significant reduction in d-HAIs after the bundle implementation, d-HAIs were associated with a 2.6-fold higher risk of death (hazard ratio [HR], 2.63; P < 0.001) regardless of the study period. Additional variables associated with increased risk of death included age (HR, 1.03; P < 0.001), baseline immunosuppression (HR based on mycophenolate versus others 0.74; P = 0.02), time since transplantation (HR, 1.003; P < 0.001), platelet count at ICU admission (HR, 0.998; P < 0.001), and sepsis as the reason for ICU admission (HR, 1.67; P < 0.001). Conclusions. The persistent risk associated with d-HAIs, despite the implementation of multifaceted control intervention actions in an ICU specialized in KTR care, underscores the need for a zero-tolerance policy toward d-HAIs.